Effect of computer workstation set-ups on muscle oxygen saturation and perceived fatigue - Radin Umar, Radin Zaid; Yin, Tiong Jing; Ahmad, Nadiah (Intelektual Pustaka Media Utama, 2024)
Multiple literatures show evidences of how office workstation set-ups can influence muscle activities. However, the relationship between the postural adoption due to workstation setup and its effect to muscle oxygen saturation among office workers is unclear. The aim of this study was to investigate trends of muscle oxygen saturation and perceived fatigue ratings between different upper limbs posture variations among representative computer users. A repeated measure experiment was conducted on 15 participants to compare the muscle oxygen saturation and perceived fatigue ratings between four different office work posture variations. Parametric and non-parametric statistical analyses were conducted to analyze significant differences on the dependent parameters. Data analysis showed statistically significant trends (p≤0.050) of lower muscle oxygen saturation in workstation set-ups in which participants were adopting raised shoulder and extended arm positions. In addition, the findings revealed that the perceived fatigue ratings on the shoulder, upper arm and lower arm are the lowest (p≤0.050) in workstation condition where subject can adopt neutral postures. The results highlight the effect of good office workstation setup and work postures to individual muscle oxygen saturation and fatigue levels.